(untitled) (e-Proceedings of the Faculty of Agriculture International Conference, 2023)
This work aimed to evaluate the effects of smoking African catfish (Clarias gariepinus) using wood fuel obtained from Neem (Azadirachta indica), Gmelina (Gmelina arborea) and African velvet tamarind (Dialium guineense) on the organoleptic properties (appearance, aroma, taste, and texture) and shelf life. The research was conducted at the fish processing unit of the Department of Fisheries and Aquaculture Management, Nnamdi Azikiwe University, Awka. A total of 12 matured catfish, 6 males and 6 females which weighed 1kg each were used for the study. After fish preparation, a total of four fish (2 males and 2 females) were smoked in three different smoking kilns using the three wood types. The organoleptic properties of the smoked catfish were analyzed by ten member panel while shelf life was determined by the period of mold and insect infestation. The results indicated that there was no significant difference (P>0.05) in the effects of these wood types on the organoleptic properties assessed. However, catfish smoked with the African velvet tamarind wood had the most preferable organoleptic qualities with a mean score of appearance (4.20±0.92a), aroma (4.30± 0.82a), taste (4.70± 0.67a), and texture (4.10± 0.86a). This was followed by catfish smoked with Gmelina wood with a mean score of appearance (2.90 ±0.88a), aroma (3.00± 0.94a) taste (3.00± 0.67a), and texture (2.90± 1.19a), while catfish smoked with Neem wood had the lowest mean score of appearance (2.00± 0.67a) and texture (2.50± 0.85a). It was also observed that there was no insect attack in all the smoked fish samples during the period of storage. However, catfish smoked with Neem wood showed the highest severity to mold attack (3.00) while fish smoked with Gmelina wood showed no mold attack (0.00). Therefore, these results indicated that fish processing with the use of these woods is effective in extending the shelf-life of smoked African catfish. As a result, the study suggests that the use of African velvet tamarind wood in smoking fish should be adopted to improve the organoleptic properties of smoked catfish which would also increase its profitability.